Evaluation of Floor Plates in the Bima City Regional General Hospital Building - Muhammad Syaiful; Wira Setiawan; Sulis Syaputri (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Floor slabs are the main structural elements that withstand the gravitational load of multi-storey buildings. This study aims to evaluate the deflection of the roof floor plate of the Bima City Regional General Hospital (RSUD) building to ensure the safety and adequacy of the structure based on service requirements. The analysis was performed numerically using SAP2000 v22 software with Shell-Thin elements. Structural data includes 8 m × 8 m slabs, 120 mm thick, concrete quality f'c = 25 MPa, fy steel quality = 420 MPa, and two-layer D10-150 reinforcement. Loading refers to SNI 1727:2020 and PPIUG 1983, with a total dead load of 4.16 kN/m² and a live load of 0.96 kN/m². The permissible deflection is calculated based on SNI 2847:2019 as δ_allow = L/240 = 33.33 mm. The results of the SAP2000 analysis showed a maximum deflection of 3.08 mm, which was far below the permissible limit, so that the roof floor plate of the Bima City Hospital was declared safe and met the requirements of the service limit country.